The EU debt crisis: Testing and revisiting conventional legal doctrine - Paul De Grauwe; Yuemei Ji; Armin Steinbach (London School of Economics and Political Science (LSE), European Institute, 2016)
Controversies surrounding the European sovereign debt crisis loom prominent in the public debate. From a legal perspective, the no-bailout rule and the ban on monetary financing constitute the main principles governing the legality review of financial assistance and liquidity measures. Interpretation of these rules are full of empirical claims. According to conventional legal doctrine, bond spreads only depend on the country's debt position, largely ignoring other causal factors including liquidity. We test the hypotheses implicit in conventional legal reasoning. We find evidence that a significant part of the surge in the spreads of the peripheral Eurozone countries was disconnected from underlying fundamentals and particularly from a country's debt position, and was associated rather strongly with market sentiments and liquidity concerns. We apply our empirical findings to the legal principles as interpreted by recent jurisprudence arguing that application of the no- bailout principle and the ban on monetary financing should be extended to capture non-debt related factors. Also, the empirical results suggest taking recourse to alternative legal grounds for reviewing the legality of anti-crisis instruments and allowing for a lender of last resort in the euro zone.
Keywords: 330